Нові дослідження захисних споруд Басівського городища - Корж, А.А. (Археологія і давня історія України, 2022)
На основі нових даних подано інформацію про
захисні споруди найбільшої поселенської пам’ятки
Посулля скіфського часу — Басівського городища.
Розглянуто питання розміщення давніх входів. Висвітлено результати польових досліджень 2020—2021 років. Defensive structures are the integral part of any fortified
settlement. Their study requires significant labor
costs, so usually the earthen constructions haven’t received
enough attention from the predecessors.
Basivka hill-fort is definitely the key settlement of
the Scythian Age in the Sula River basin. Its total area
is approximately 170 ha. The central, residential part
is located on three well-fortified capes. Not all fortification
areas were created simultaneously but had developed
dynamically in time and space. Successful usage
of natural topographic features at this settlement is
combined with the basics of defense tactics.
Modern agricultural activity and dwelling construction
led to significant damage,and in some places to
the destruction of earthen structures of Basivka hillfort.
This is especially true of the Great Outer Rampart
which is well-preserved only in the eastern part.
The complexity of the modern terrain and the significant
forest cover were the determining factors that
hindered the preparation of the most accurate topographic
plan of this site. The paper presents a new plan
of central fortifications but it also needs to be revised
which is a matter of the future.
A separate issue of the work is devoted to the placement
of ancient entrances, which, like the fortification
in general, could change over time and move from the
main to the role of secondary ones.
The paper highlights the results of excavations of
the Great Basivka Rampart which were conducted in
2020—2021. It is ascertained that the defensive structures
cover the cultural layer of the settlement. In general,
valuable information was obtained regarding the
development of fortifications in the Ukrainian Forest-
Steppe of Dnieper Left-Bank area in the Scythian Age.